EXPERIMENTAL STUDY ON SPLITTING TEST ON LIGHT WEIGHT CONCRETE USING BAMBOO FIBER AS AGGREGATE - M. Heri Zulfiar; M. Riang Endarto (Institut Teknologi Sepuluh Nopember (ITS), 2011)
Static load of construction element is the most general problem at civil constructon design, the use of bamboo as subtitution of agregate is the one of solution to reduce unit weight and static load of construction element. Based on consideration of structure analysis, bamboo is suitable as alternative of construction material. Focus of the research is type of bamboos fiber that used as concrete mix. The research observations consist of unit weight, compressive and cracking strength using flowing concrete method. The research using bamboos fiber at proportion 0/100% (Normal), 20/80%, 40/60%, 60/40%, 80/20% and 100/0% of conventional agregate. The speciments shape is concrete cylinder (15 cm diameter and 30 cm height) and speciment identification and cracking strenght be perform after 14 days treatment. The result of reasearch indicate decrease of cracking strenght and non linier relationship strength-strain characteristic.